2022
DOI: 10.3389/fmed.2022.869190
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of FibroScan-Aspartate Aminotransferase (FAST) Score and Other Non-invasive Surrogates in Predicting High-Risk Non-alcoholic Steatohepatitis Criteria

Abstract: Identification of non-alcoholic steatohepatitis (NASH) with high activity and fibrosis is a major priority in patients with non-alcoholic fatty liver disease. We validated the predictive value of the FibroScan-aspartate aminotransferase (FAST) score and other non-invasive fibrosis surrogates in predicting high-risk NASH criteria. This multicenter retrospective study recruited 251 biopsy-proven non-alcoholic fatty liver disease (NAFLD) patients (132 [52.6%] men) between 2011 and 2014. The FAST score was calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…3 , 4 ). Lee et al demonstrated that FAST score and APRI were significantly involved in the degree of fibrosis and steatosis [ 29 ]. This report supports our data that pemafibrate might improve liver function and fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…3 , 4 ). Lee et al demonstrated that FAST score and APRI were significantly involved in the degree of fibrosis and steatosis [ 29 ]. This report supports our data that pemafibrate might improve liver function and fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…In the current era of potent AVT where the virologic effects can be easily suppressed, most of the recently established systems adopted the presence of baseline cirrhosis or fibrotic burden, and generally demonstrated high negative predictive values to exclude HCC development within about 10 years [38]. However, because cirrhosis itself is a strong predictor [39], the predictive power of the proposed models is expected to decrease somewhat in the cirrhosis group, which has a common fibrotic burden [40].…”
Section: Discussionmentioning
confidence: 99%
“…FAST™ performed better than other non-invasive algorithms for the diagnosis of at-risk NASH[ 104 , 105 ]. Results have shown that the FAST score had the highest area under curve for the most high-risk NASH criteria as well as liver stiffness showing a consistently acceptable performance in predicting NASH[ 106 ].…”
Section: Introductionmentioning
confidence: 99%